Tailorable fabrication of optical active nanomaterials for bio-applications - Mengna Zhang; Shuaishuai Wei; Huiqi Huang; Haihui Sun; Liping Zhang; Wenhan Zhang; Yuan Zhao; Wei Ma (Biofunctional Materials)
The unique properties of nanoscale materials exhibiting chirality, such as their catalytic, optical and photothermal capabilities, have been recognized for their exceptional potential in bio-applications. The optical active nanomaterials have attracted significant attention due to their valuable contributions to the fields of biocatalysis, biosensing and nanomedicine, marking a period of notable progress and innovation. In this review, we delve into the most recent advancements in this rapidly evolving field, aiming to provide a thorough insight into the progress made with optically active nanomaterials and to inspire further advancements in bio-applications.